2015
DOI: 10.1007/s00228-015-1982-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring of second-generation antipsychotics in pediatric patients: an observational study in real-life settings

Abstract: Our study described the distribution of plasma levels of SGAs in a real-life setting involving pediatric patients, significantly increasing the amount of available data for this fragile population. If confirmed in larger dataset, these data may contribute to the definition of optimal therapeutic window for risperidone and aripiprazole plasma levels in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
6
11
1
1
Order By: Relevance
“…The extrapolation of therapeutic reference ranges -which have been established in adult patients -to paediatric patients, especially to young children, has to be investigated for every single substance, as preliminary TDM studies in paediatric neuropsychiatry provided divergent results. Fortunately, however, several studies have demonstrated similar therapeutic reference ranges for children/adolescents and adults (e. g., sertraline [1177], aripiprazole [949,1311], fluvoxamine [677]). For most substances, a high interindividual variability in drug concentrations after administration of the same dose was shown in children and adolescents.…”
Section: Recommendationmentioning
confidence: 99%
“…The extrapolation of therapeutic reference ranges -which have been established in adult patients -to paediatric patients, especially to young children, has to be investigated for every single substance, as preliminary TDM studies in paediatric neuropsychiatry provided divergent results. Fortunately, however, several studies have demonstrated similar therapeutic reference ranges for children/adolescents and adults (e. g., sertraline [1177], aripiprazole [949,1311], fluvoxamine [677]). For most substances, a high interindividual variability in drug concentrations after administration of the same dose was shown in children and adolescents.…”
Section: Recommendationmentioning
confidence: 99%
“…Its half‐life of up to 37 hr means that steady state and sustained efficacy for CINV may take a few days to achieve. Studies suggest no appreciable difference in olanzapine pharmacokinetics between children and adults …”
Section: Clinicial Considerationsmentioning
confidence: 99%
“…Concomitant usage of metoclopramide and olanzapine is contraindicated due to additive risk for EPS. Long‐term risk is unclear given relatively recent availability of olanzapine and ongoing research and phase 4 long‐term surveillance safety trials …”
Section: Cautionsmentioning
confidence: 99%
See 2 more Smart Citations